2020
DOI: 10.3390/nu12061755
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Sarcopenia—What Do We Know?

Abstract: Muscle health is important for the functionality and independence of older adults, and certain nutrients as well as dietary patterns have been shown to offer protective effects against declines in strength and function associated with aging. In this paper, micronutrients, macronutrients, and food groups have been reviewed, along with their studied effects on the prevalence and incidence of sarcopenia, as well as their ability to preserve muscle mass and optimize physical performance. Randomized controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
141
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(155 citation statements)
references
References 138 publications
(189 reference statements)
2
141
0
12
Order By: Relevance
“…With regard to other dietary components, further aspects should be explored in T2DM with sarcopenia; in fact, in non-diabetic individuals, there are some promising data regarding the role of vitamin D and sarcopenia, but it is unclear whether the dose, frequency of dose, or length of treatment impacts the efficacy of vitamin D on improving muscle mass or function [ 109 ]. Furthermore, selenium and magnesium have been studied as supplements in clinical trials and in the diet, and they appear to demonstrate a potential association with physical activity, muscle performance, and bone health in older individuals [ 109 , 110 ]. Following the Mediterranean diet and higher consumption of fruits and vegetables have been associated with improved physical performance and protection against muscle wasting, sarcopenia, and frailty [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to other dietary components, further aspects should be explored in T2DM with sarcopenia; in fact, in non-diabetic individuals, there are some promising data regarding the role of vitamin D and sarcopenia, but it is unclear whether the dose, frequency of dose, or length of treatment impacts the efficacy of vitamin D on improving muscle mass or function [ 109 ]. Furthermore, selenium and magnesium have been studied as supplements in clinical trials and in the diet, and they appear to demonstrate a potential association with physical activity, muscle performance, and bone health in older individuals [ 109 , 110 ]. Following the Mediterranean diet and higher consumption of fruits and vegetables have been associated with improved physical performance and protection against muscle wasting, sarcopenia, and frailty [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, selenium and magnesium have been studied as supplements in clinical trials and in the diet, and they appear to demonstrate a potential association with physical activity, muscle performance, and bone health in older individuals [ 109 , 110 ]. Following the Mediterranean diet and higher consumption of fruits and vegetables have been associated with improved physical performance and protection against muscle wasting, sarcopenia, and frailty [ 109 ]. The supplementation of the branched-chain amino acid, leucine, or leucine-enriched protein is one of the most common interventions for treating sarcopenia in older individuals [ 111 , 112 ], and evidence reported that administration of leucine or leucine-enriched proteins (range 1.2–6 g leucine/day) is well-tolerated and significantly affects sarcopenia in elderly individuals, improving muscle strength, lean mass content, and walking speed although these effects depend on sarcopenia criteria and the patients’ characteristics [ 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, the beneficial impacts of plant-derived proteins on indices of muscle health are not fully explained. It has been suggested that alkaline plant-based diets, rich in minerals such as potassium and magnesium, may favour maintenance of muscle mass and function in older adults [60]. Further research is warranted in order to unravel links between plant-derived proteins and muscle health.…”
Section: Discussionmentioning
confidence: 99%
“…A secondary progressive loss of muscle mass or sarcopenia in chronic diseases is an increasing medical issue, particularly in the ageing population of developed countries [ 1 , 2 ]. The underlying causes are frequently multifactorial, such as aging-dependent inactivity and malnutrition.…”
Section: Introductionmentioning
confidence: 99%